VALUASI EKONOMI HUTAN MANGROVE DI SUNGAI MAS DESA PEMANGKAT KOTA KABUPATEN SAMBAS - Hidayat, Ari; roslinda, emi; Lumangkun, Agustine (Universitas Tanjungpura, 2016)
Mangrove forest ecosystem is capable to fulfill almost all human necessities by tangible and intangible value contribution it has. The purpose of this research is to find out the Direct Use Value (DUV) on mangrove forest in Sungai Mas, Sebangkau District, Sambas Regency which is held on Â± 4 (four) weeks effectively. The method used in this census (data collecting), with the number of respondents 188 head households. Valuation of the varieties used by people in Sungai Mas use market price method for firewood, fruit and water product. The research showed total economical value of the mangrove forest on Sungai Mas valued Rp21.123.386.000.-/year contained of firewood Rp. 44.016.000.-/year, fruitsrp Rp. 4.100.000,-/year, scallop Rp. 3.610.800.000,-/year, crab Rp1.355.750.000-/year, prawn Rp. 11.655.000.000,-/year, and fish Rp. 4.453.720.000,-/year. The economical value of mangrove forest on Sungai Mas is really high. Therefore it is necessity to protect the mangrove forest such as reforestation either by government agencies or by the people awareness. So the current economical value remains exist and even gains to welfare the society. Also, the product from aquatic is also dominating. This shows that even without doing forest destruction people can still receive the economical benefit. Keywords : Sungai Mas Mangrove Forest, Total Economical Value, Use Value